From Projection to the Construction of the Perceptual Environment: Syn, by Rhizomatiks and ELEVENPLAY (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
This article investigates how immersive audiovisual environments mediated by computational systems reconfigure the relationships between body, space, and perception in contemporary performance, within the context of the expanded scene. It starts from a shift in projection mapping practices, which move beyond surface application to become dynamic and responsive environments. As a case study, it analyzes Syn: Unfolded Horizons of Bodily Senses, by Rhizomatiks in collaboration with ELEVENPLAY. Drawing on media performance, intermediality, and scenography as a relational system, the study examines how the integration of motion sensors, real-time processing, projection, lighting, and sound produces an unstable perceptual field. It argues that the image becomes a constitutive element of spatiality and sensory experience, reshaping perceptual conditions. Finally, it critically addresses the ornamental use of audiovisual technologies in contemporary performance. The article is grounded in theoretical contributions that examine the relationships between technology, performance, and perception, with particular emphasis on Steve Dixon’s reflections on digital performance and the integration of computational systems into performative practices, Sarah Bay-Cheng’s discussions on intermediality and the dissolution of boundaries between media and theatre, and Rachel Hann’s understanding of scenography as a relational system oriented toward the production of spatiality and experience. These perspectives are complemented by materials produced by the collective Rhizomatiks itself, whose records and documents on the analyzed work provide insight into the modes of spatial articulation.
Keywords: Rhizomatiks; escena expandida; proyección mapeada